2017
DOI: 10.1007/s40520-017-0848-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between plasma interleukin-15 levels and sarcopenia in outpatient older people

Abstract: A low level of plasma IL-15 is associated with sarcopenia in outpatient older people. Further longitudinal and prospective studies are needed to evaluate changes in IL-15 over time together with muscle mass and strength or therapeutic potential of IL-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…IL-15 levels are increased by exercise in humans (Rinnov et al, 2014 ). On the other skeletal muscle aging and sarcopenia are associated with low levels of IL-15 (Yalcin et al, 2018 ). Here, we show that exercise reduced IL-15 mRNA level in aged control and Nmrk2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 levels are increased by exercise in humans (Rinnov et al, 2014 ). On the other skeletal muscle aging and sarcopenia are associated with low levels of IL-15 (Yalcin et al, 2018 ). Here, we show that exercise reduced IL-15 mRNA level in aged control and Nmrk2 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-15 receptor signalling subunit IL2RB expression was 80% lower in older muscle, suggesting that the intracellular promyogenic effects of IL-15 may be blunted in the elderly. In a separate study, plasma IL-15 concentrations were found to be lower in sarcopenic compared to nonsarcopenic older adults and inversely correlated with sarcopenic state and body mass index (BMI) [50]. With regard to adiposity and IL-15 expression, obese individuals present with lower serum IL-15 than normal-weight individuals and IL-15 knockout in mice results in weight gain [139].…”
Section: Interleukin-15mentioning
confidence: 95%
“…In the mice muscle and serum, IL-15 protein levels decline progressively with advanced age (Quinn et al, 2010). Further, Yalcin et al (2018) demonstrated that the level of IL-15 is significantly lower in patients with sarcopenia compared to non-sarcopenic old people. A study conducted on a C2C12 muscle cell line presented the protective effects of IL-15 against H 2 O 2 -iduced oxidative stress.…”
Section: Endocrine Function Of the Skeletal Muscle And Neurodegenerationmentioning
confidence: 96%